Study the role of hepcidin in diagnosis of iron deficiency anemia in young females of northern India - ., Shaveta; Bansal, Sanjiv Kumar; Patel, Seema (International Journal of Research in Medical Sciences, 2020)
Background: Iron deficiency is one of the most common nutritional disorder. Maintenance of body iron status is an integral part of healthcare in young female of reproductive age group. Thereby early detection could lead to early intervention and reduce its comorbidity. Indeed, an ideal screening test should be capable of identifying iron deficiency long before developing anemia. Henceforth, the present study was aimed to determine utility of serum hepcidin in iron deficiency and to access the baseline value of hepcidin in young female. Methods: This sectional study was conducted in the Department of biochemistry SGT Medical College Hospital and Research Institute, Budhera, Gurugram. It included non-pregnant female students of age 18-25 years with normal RBC indices and hemoglobin >12 gm%. Estimation of serum hepcidin-25 was by ELISA. Results: The reference range of hepcidin established in this study was 12.14-139.89 ng/ml for females with the mean being 42.4±29.13 ng/ml. It showed higher discriminating power in evaluating iron status in young healthy women (AUC 0.984) with best combination of diagnostic sensitivity (95.7%) and specificity (93.2%) at a cut off of >15.7 ng/ml. Serum hepcidin identified 17% of young healthy females with normal hemoglobin to have functional or storage iron deficiency. Conclusions: The prevention of iron deficiency anemia remains insufficient worldwide especially among underprivileged women and children Therefore, estimation of serum hepcidin may be considered as a valuable tool in assessing iron status in young healthy female population who are the prime target group for iron supplements to reduce comorbidity associated with iron deficiency and anemia.